Estudo fitoquímico e biológico de espécies amazônicas: Pradosia huberi (Ducke) Ducke (Sapotaceae) e Licania macrophylla Bent. (Chrysobalanaceae) - Medeiros, Fernando Antônio de (2008)
The use of plants as a treatment method has gained prominence and became fashionable in the world. In Brazil is not different. In recent years some brazilian states has been implementing phytotherapy as an alternative therapy for the public health. However there are some drawbacks as the lack of scientific information that supporting traditional knowledge of some species. The Licania macrophylla Benth species belongs to the Chrysobalanaceae family and is known popularly as "anauera" or "anuera." The stem bark of this species is used in the state of Amapá like amebicide as antidiarrheal. The Pradosia huberi Ducke species belongs to the Sapotaceae family, and is popularly called "fresh bark" or "stick candy ' and its stem bark is used by Amazonian peoples to assist in the treatment of stomach problems and indigestion. However the use of the stem bark of these species in the preparation of herbal formulation or even home preparation is a predatory practice, because recovery of the damage caused by removal of the bark takes years to rebuild, if not eliminates the specimen. The aim of this work was the phytochemical and biological study of the Licania macrophylla Benth and Pradosia huberi (Ducke) Ducke species and compare the chemical composition of leaves and stem bark of both species, so as to suggest that you can replace the use of shells stem by the leaves, and thus contribute to the conservation of the species under discussion. The species studied were collected at Porto Grande - Amapá - Brazil and specimens are deposited in the Herbarium Amapaense HAMAB IEPA. The phytochemical study of the stem bark of the L. macrophyla Benth (Chrysobalanaceae) species led to the isolation of (-)-4'-O-methyl-epigallocatechin-3'-O-α- L-raminosídeo (LM-1), (-)-4'-methyl-epigallocatechin (Lm -2), while the leaves were isolated pheophytin A (Lm-3), 132-hydroxy-(132-S) pheophytin A (Lm-4), pheophytin B (Lm-5), β-sitosterol (Lm-6a ), stigmasterol (Lm-6b), β-sitosterol-O-glycoside (Lm-7), alcohol betulínco (Lm-8) and oleanolic acid (Lm-9), the first not reported in the literature. From species was isolated Pradosia huberi 2,3-dihidromiricetina-3-α-LO-raminosídeo (Ph-1) and leaves the fatty ester erythrodiol (Ph-2), ester of fatty oleanolic acid (Ph-3) fatty ester betulínco acid (Ph-4) and espinasterol (Ph-5), all identified by techniques 1H NMR and 13C single and two-dimensional and comparisons with published literature. Evaluation of antidiarrhoeal activity of the methanol extract of the stem bark (EMC) of L. macrophylla showed that this does not interfere with intestinal parameters: modulation of normal defecation, cathartic agent-induced diarrhea and intestinal transit stimulated. But EMC had to be active against Staphylococcus aureus ATCC 25928, Pseudomonas aeruginosa ATCC 25853 and Escherichia coli ATCC 10536, a result similar to that seen with Lm-1. The methanol extract of leaves (EMF) of L. macrophylla was active against the twelve bacterial strains tested, a result similar to that observed with Lm-4 and Lm-9. Regarding the chemical constituents isolated from the stem bark and leaves in two species can state that are not similar. Regarding the antimicrobial activity of EMC and EMF were similar, suggesting that the activity is antidiarrhoeal proven that one should only antimicrobial can be no substitution of the stem bark of the leaves.